(3edGeM GdefGN GdGSJKeGQj aj GdLRGFQ (B:s (3ebheGJ GdLPH hYhGed GdWQO (B/s - (3jMjGhj, YeQ s ((3GdLRGFQ (B: s (3OGQ EjdjGA ddfTQ hGdJhRjY(B, s, 2024)
(3GhdG (B: (3YehejGJ Mhd efGN GdGSJKeGQ , YdGbI efGN GddGSJKeGQ HGdJWhQGJ GdYGdejI GdQGgfI , KGfjG (B: (3YehejGJ Mhd GdGSJKeGQ GdGLfHj GdeHGTQ , GdfXQjGJ GdeaSQI dOhGaY GdGSJKeGQ GdGLfHj GdeHGTQ h KGdKG (B: (3NdajI JGQjNjI Mhd GdGbJUGO GdLRGFQj ddaJQI (B(1962-2002) (3, JMdjd hGbY efGN GdGSJKeGQ aj GdLRGFQ (B.s
(3GdeQGLY U(B.273s